Effect of cardiopulmonary bypass on platelet mitochondrial respiration and correlation with aggregation and bleeding: a pilot study. (September 2016) - Mazzeffi, Michael; Lund, Lindsey; Wallace, Karin; Herrera, Anthony V; Tanaka, Kenichi; Odonkor, Patrick; Strauss, Erik; Rock, Peter; Fiskum, Gary
Background: Cardiopulmonary bypass (CPB) may cause platelet dysfunction, contributing to bleeding. There are no investigations of how CPB affects platelet mitochondrial respiration and what correlation this has with platelet aggregation and bleeding. Methods: We studied platelet mitochondrial respiration and aggregation in eighteen adult cardiac surgery patients having CPB. The relationships between respiration, aggregation and postoperative bleeding were analyzed. Results: Platelet respiration, reflected by the respiratory control ratio (RCR), was unchanged after CPB (mean difference in RCR= −0.02 (95% CI=−1.45 to 1.42), p=0.98). Further, there were no significant relationships between indexed adenosine diphosphate (ADP) or thrombin receptor-activating peptide (TRAP)-induced aggregation and the RCR (p=0.12 and p=0.41). Only post-CPB ADP - induced aggregation correlated with 24-hr chest tube output (p=0.04), but indexing for platelet count attenuated the effect (p=0.07). Conclusion: Platelet mitochondrial respiration is preserved after CPB and is not correlated with aggregation or bleeding. Only post-CPB, ADP-induced aggregation correlates with postoperative bleeding.